Not for Profit : Why Democracy Needs the Humanities - Updated Edition - Nussbaum, Martha C. (Martha Craven), 1947- (Book collections on Project MUSE., 2016)
"In this short and powerful book, celebrated philosopher Martha Nussbaum makes a passionate case for the importance of the liberal arts at all levels of education. Historically, the humanities have been central to education because they have been seen as essential for creating competent democratic citizens. But recently, Nussbaum argues, thinking about the aims of education has gone disturbingly awry in the United States and abroad. We increasingly treat education as though its primary goal were to teach students to be economically productive rather than to think critically and become knowledgeable, productive, and empathetic individuals. This shortsighted focus on profitable skills has eroded our ability to criticize authority, reduced our sympathy with the marginalized and different, and damaged our competence to deal with complex global problems. And the loss of these basic capacities jeopardizes the health of democracies and the hope of a decent world. In response to this dire situation, Nussbaum argues that we must resist efforts to reduce education to a tool of the gross national product. Rather, we must work to reconnect education to the humanities in order to give students the capacity to be true democratic citizens of their countries and the world. In a new preface, Nussbaum explores the current state of humanistic education globally and shows why the crisis of the humanities has far from abated. Translated into over twenty languages, Not for Profit draws on the stories of troubling--and hopeful--global educational developments. Nussbaum offers a manifesto that should be a rallying cry for anyone who cares about the deepest purposes of education."